Kepadatan dan Dominasi Pinjal pada Beberapa Jenis Tikus dan Habitat di Daerah Enzootik Pes di Kabupaten Pasuruan, Jawa Timur - Cahyaningrum, Winda Rahma; Wardani, Dita Pratiwi Kusuma; Ristiyanto, Ristiyanto; Almanfaluthi, Muhammad Luthfi; Handayani, Farida Dwi (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Fleas are hemophagous insects that spread the Yersinia pestis bacteria that causes bubonic plague through the bites of infected fleas. The purpose of this study was to determine the density, dominance, and infestation of larvae in several types of rodents and habitats in the Pes enzootic area. This research was conducted in May–June 2023 in Pasuruan Regency, East Java. The data analysis method used was descriptif. Samples of rat fleas were taken from rats captured in residential, garden, and forest habitats. The results showed that six species of small mammals were captured, namely, the Muridae family consisting of Niviventer fulvescens, Rattus exulans, Rattus tanezumi, and Rattus tiomanicus; the Erinaceidae family, namely Helomys suillus; and the Soricidae family, namely Suncus murinus, with the highest trap success in residential habitats by 10.9% and the highest density of rats in residential and garden habitats. The larval species obtained were Xenopsylla cheopis and Stivalius cognatus, with the highest flea infestation in the rat species Rattus exulans female (300%) and Rattus tanezumi female (64.2%).